A cross-country investigation of customer transactions from online to offline channels. Issue 12 (3rd September 2020) - Huang, Chien-Che; Chang, Yu-Wei; Hsu, Ping Yu; Prassida, Grandys Frieska
Abstract : Purpose: The purpose of this study is to investigate multichannel integration of hotels and online travel agencies (OTAs) and to compare consumer behavior between China and Indonesia in the context of online to offline (O2O) commerce. We examine how the services, brand and market share of OTAs influence behavioral intentions in both online and offline channels. SERVQUAL, theory of reasoned action and the halo effect are integrated to develop the research model. Design/methodology/approach: To investigate Chinese and Indonesian customers' experiences and behavioral intention of OTAs and hotels, the customers who booked hotels using OTAs were invited to participate in the questionnaire survey. This study collected 336 and 305 data from China and Indonesia, respectively. A partial least squares structural equation modeling technique was used to test and compare the research hypotheses and model between China and Indonesia. Findings: The results compare the similarities and differences of cross-country customer experiences and behavioral intentions of OTAs and hotels. The effect of website service quality on online satisfaction, the effect of online satisfaction on offline confirmation and the effects of offline confirmation and booking intention on patronage intention are significant and positive in both countries. Website service quality is positively associated with booking intention for Indonesia but not for China. The relationship between perceived size and booking intention is significant for China but not for Indonesia. The findings provide insights into the development of O2O commerce for global markets and multichannel strategies between OTAs and hotels. Originality/value: With the development of O2O commerce, increasingly more hoteliers are opening up online and offline sales channels by cooperating with OTAs. Although several cross-country studies have investigated consumer behavior or behavioral intentions, behavioral settings are based on online or offline channels rather than the integration of both channels. Although some research has studied the integration or competition of OTAs and hotels, none of these studies have investigated the issues from the perspective of country comparison. This study provides the understanding of how customers in different countries and with different backgrounds react to the same e-commerce development, especially the cooperation of OTA and hotels.